2005
DOI: 10.1016/s0002-9440(10)62989-6
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonitis and Multi-Organ System Disease in Common Marmosets (Callithrix jacchus) Infected with the Severe Acute Respiratory Syndrome-Associated Coronavirus

Abstract: Severe acute respiratory syndrome (SARS) is a significant emerging infectious disease. Humans infected with the etiological agent, SARS-associated coronavirus (SARS-CoV), primarily present with pneumonitis but may also develop hepatic, gastrointestinal, and renal pathology. We inoculated common marmosets (Callithrix jacchus) with the objective of developing a small nonhuman primate model of SARS. Two groups of C. jacchus were inoculated intratracheally with cell culture supernatant containing SARS-CoV. In a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 36 publications
1
108
1
2
Order By: Relevance
“…Moreover, the disease in NHP models appears self-limiting and different from the human disease (148). The common marmoset model seems promising and should be evaluated further (149).…”
Section: Animal Models Of Sars-cov Infectionmentioning
confidence: 99%
“…Moreover, the disease in NHP models appears self-limiting and different from the human disease (148). The common marmoset model seems promising and should be evaluated further (149).…”
Section: Animal Models Of Sars-cov Infectionmentioning
confidence: 99%
“…Before infection, they were examined clinically and determined to be healthy by a registered veterinarian and were placed in negative-pressurized glove boxes. Four cats and 4 ferrets were inoculated intratracheally in 1-5 seconds under ketamine anesthesia with 10 6 TCID 50 of SARS-CoV. The animals were checked daily for clinical signs.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…20 The distribution of ACE2 in human tissues corresponds largely to the cell types in which SARS-CoV replication has been observed: in addition to type II pneumocytes and bronchial epithelial cells, ACE2 expression has been observed in type I pneumocytes and endothelial cells as well as smooth muscle cells of blood vessels, but not alveolar macrophages. 15,37 Since the appearance of SARS, several animal models have been developed for SARS-CoV infection in humans: SARS-CoV infection in macaques, 6 marmosets, 10 mice, 8,31 golden Syrian hamsters, 32 rats, 24 cats, and ferrets. 22 Subbarao and Roberts 35 reviewed the advantages and disadvantages of the above animal models.…”
mentioning
confidence: 99%
“…Animal models described to date include several inbred mouse strains, hamsters, civet cats, ferrets, cats, or nonhuman primates (Fouchier et al, 2003; Glass et al, 2004; Greenough et al, 2005; Hogan et al, 2004; Lawler et al, 2006; Martina et al, 2003; McAuliffe et al, 2004; Qin et al, 2005; Roberts et al, 2005a; 2005b; 2007; Rowe et al, 2004a; Subbarao et al, 2004; ter Meulen et al, 2004; Wu et al, 2005). The timecourse of virus replication in these small animal models is significantly more rapid than that observed in human infections (Roberts et al, 2008) and no model fully reproduces the clinical illness or the pathology observed in humans.…”
Section: Introductionmentioning
confidence: 99%